Sistem Pengendalian Persediaan Barang Berbasis Website dengan Metode Economic Order Quantity dan Reorder Point - Faiz, Muhammad Nur; Rachmawati, Seppy Ayu; Syafirullah, Lutfi (Jurnal Ilmu Komputer; Vol 14 No 2 (2021): Jurnal Ilmu KomputerDO - 10.24843/JIK.2021.v14.i02.p06, 2021)
Inventory of goods is one of the important factors in developing a business. This inventory affects operational costs. Excess inventory will also lead to greater storage and maintenance costs. Meanwhile, a lack of inventory will cause stock out. Website Inventory information system with the Economic Order Quantity (EOQ) and ReOrder Point (ROP) method can be an alternative to overcome this problem. This information system was developed using the SDLC (System Development Life Cycle) development method. The programming language used is PHP Hypertext Preprocessor, MySQL as database, and Xampp as a web server. EOQ method can determine the level of inventory required by the company. Meanwhile, the ROP to determine the time an item is in the warehouse must be added to the inventory before it runs out. This research results that the determination of the quantity of purchase inventory using the EOQ method and the ROP method is more efficient and the inventory becomes more optimal so that the store can get maximum profit. The results of the system functionality test show that this system works very well